KAJIAN HUKUM TENTANG EFEKTIVITAS PENGATURAN MASYA- RAKAT HUKUM ADAT MENGENAI PERLINDUNGAN HAK-HAK TRADISIONAL DALAM PERSPEKTIF HAK ASASI MANUSIA DI INDONESIA - Dicky Wahyudi; Emilda Firdaus; Muhammad A. Rauf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
One of the implementations of people's sovereignty is the implementation of theprotection of the traditional rights of indigenous and tribal peoples based on humanrights, abbreviated as HAM. Indonesia is known as a nation rich in customs and culture.The existence of indigenous peoples who have even existed since before the unitarystate of the Republic of Indonesia existed, it is still difficult to get recognition andprotection, including protecting their customary territories.This type of research can be classified into normative research, namely findingthe truth of coherence, that is, are there legal rules according to legal norms and arethere norms in the form of orders or prohibitions that are in accordance with legalprinciples and whether a person's actions are in accordance with legal norms or in legalresearch called research on legal principles (not just in accordance with the rule of law)or legal principles.From the results of the research problem there are two main things that can beconcluded. First, the regulation on the protection of indigenous peoples is a legal policyin an effort to protect the human rights of indigenous peoples made by the Governmentin the form of laws and regulations based on philosophical, sociological and juridicalaspects, but the current ones are not optimal and in accordance with Pancasila and whatis aspired to. by the 1945 Constitution of the Republic of Indonesia.,. Second, the idealconcept of legal politics to protect the rights of indigenous peoples based on humanrights principles is to harmonize and synchronize existing laws and regulations becausethe political law to protect the rights of indigenous peoples in the regions does not yethave clear regulations. The author's suggestion is First, the President together with theDPR must immediately pass the Draft Law on indigenous peoples so that the legalcertainty for the recognition of indigenous peoples is more secure. Second, the NationalLegal Development Agency must review the laws and regulations governing indigenousand tribal peoples so that there are no multiple interpretations of the rights of indigenousand tribal peoples so that there are no more crimes against the human rights ofindigenous and tribal peoples committed by entrepreneurs using instruments.Keywords: Keywords: -Customary Law Society, -Legislation, -Legal Politic